2022
DOI: 10.1186/s10194-021-01376-7
|View full text |Cite
|
Sign up to set email alerts
|

Eptinezumab treatment initiated during a migraine attack is associated with meaningful improvement in patient-reported outcome measures: secondary results from the randomized controlled RELIEF study

Abstract: Background Demonstrating therapeutic value from the patient perspective is important in patient-centered migraine management. The objective of this study was to investigate the impact of eptinezumab, a preventive migraine treatment, on patient-reported headache impact, acute medication optimization, and perception of disease change when initiated during a migraine attack. Methods RELIEF was a randomized, double-blind, placebo-controlled trial condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…This early efficacy finding is consistent with a previous post hoc analysis of data from PROM-ISE-2, where more patients treated with eptinezumab than those receiving placebo responded as early as month 1 following infusion [21]. Additionally, eptinezumab has been associated with rapid improvements of health-related quality of life, even when administered during a migraine attack, with eptinezumab significantly improving PROs after 4 weeks compared with placebo [22]. The results reported here support and are consistent with previously published results from the double-blind, placebo-controlled PROMISE-2 trial demonstrating that the preventive treatment effect of eptinezumab significantly reduces monthly migraine days from baseline relative to placebo (100 mg, -7.7 days, 300 mg, -8.2 days; placebo, -5.6 days), is sustained over a full 24 weeks, and has an acceptable safety profile in patients with chronic migraine [11,23].…”
Section: Discussionsupporting
confidence: 88%
“…This early efficacy finding is consistent with a previous post hoc analysis of data from PROM-ISE-2, where more patients treated with eptinezumab than those receiving placebo responded as early as month 1 following infusion [21]. Additionally, eptinezumab has been associated with rapid improvements of health-related quality of life, even when administered during a migraine attack, with eptinezumab significantly improving PROs after 4 weeks compared with placebo [22]. The results reported here support and are consistent with previously published results from the double-blind, placebo-controlled PROMISE-2 trial demonstrating that the preventive treatment effect of eptinezumab significantly reduces monthly migraine days from baseline relative to placebo (100 mg, -7.7 days, 300 mg, -8.2 days; placebo, -5.6 days), is sustained over a full 24 weeks, and has an acceptable safety profile in patients with chronic migraine [11,23].…”
Section: Discussionsupporting
confidence: 88%
“…Changes from baseline in HIT-6 total score did not show a clear trend of increasing improvement with poorer baseline optimization; however, eptinezumab treatment was associated with numerically larger improvements than placebo in HIT-6 total score at week 4, similar to the mTOQ-6 [16]. The most pronounced effects were noted in very poorly optimized patients, which may include patients who are potentially stuck in the vicious cycle of medication overuse and MOH.…”
Section: Discussionmentioning
confidence: 81%
“…However, the design of RELIEF limits the ability to connect the preventive migraine efficacy of eptinezumab to the changes observed on patient-reported outcomes, though it has been shown that the preventive effect of eptinezumab can be observed as early as the day after infusion [28]. These analyses did not exclude patients who did not experience a new migraine during the 4-week treatment period, which occurred more frequently in the eptinezumab group than in the placebo group [16]. The effects of not experiencing another migraine attack in the study may over-or underestimate patient-reported evaluation of acute treatment optimization.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eptinezumab is the only intravenous anti-CGRP(-R) mAb. Eptinezumab reaches its maximum serum concentration within minutes to hours, whereas other antibodies require up to one week to reach their maximum levels (74)(75)(76). Notably, in an acute migraine treatment setting, switching between drugs within the same class (e.g., triptans) is an accepted strategy.…”
Section: Switching Between New Therapiesmentioning
confidence: 99%